The Effects of Macroeconomic, Fundamental, and Technical Variables on the Infobank15 Stock Price Index During the January 2020 – December 2024 Period - Suwandi, Bryan Zelig; Sakti, Rachmad Kresna (Contemporary Studies in Economic, Finance and Banking, 2025)
This study aims to analyze the effects of Macroeconomic Variables, namely Inflation and Interest Rates, Fundamental Variable namely Net Interest Margin, and Technical Variable namely Exponential Moving Average 21 on The INFOBANK15 Stock Price Index in the range January 2020 to December 2024. This research uses a quantitative approach, using secondary data sourced from Otoritas Jasa Keuangan, Bank Indonesia, Bursa Efek Indonesia, and Yahoo Finance. The data analysis tool uses Panel Data Regression and is processed with Stata 17 software. The results showed that the Inflation, Net Interest Margin, and Exponential Moving Average 21 Variables had a positive and significant effect on The INFOBANK15 Stock Price Index, while the Interest Rate Variable had a negative and significant effect on The INFOBANK15 Stock Price Index.